Tetracycline degradation by the Co3O4/peroxymonosulfate system: Effect of calcination temperature - Xinfeng Zhu; Jiaxuan Li; Yunlong Wang; Tuo Wang; Mengyao Shi; Linlin Chang; Chaohai Wang; Kai Wang; Libin Jiang; Dandan Pang; Zhongxian Song; Shiqiang Yin; et al. (Chemical Physics Impact, 2024)
The widespread antibiotic use is accompanied by antibiotic resistance. A large number of antibiotic pollutants enter the water, seriously endangering the ecological environment and human health. In this study, cobalt-based materials are used to activate persulfate to treat antibiotics in wastewater based on advanced oxidation. Co3O4 is obtained at different temperatures by the one-step roasting method, eliminating the complicated preparation of traditional materials which require a large amount of reagents, generating a large amount of wastewater, and complex large-scale preparation. XRD and Raman results indicate the materials’ good crystallinity and purity. XPS and SEM indicated that the appropriate calcination temperature promoted the formation of Co2+, which was conducive to the activation of PMS for the oxidation of TCH. The catalytic activity of the materials is evaluated using tetracycline (TCH). Results suggest that 90.01 % of TCH is removed after 30 min using 0.8 g/L Co3O4–350 °C, 0.4 g/L persulfate (PMS), 25 °C, and initial pH. Moreover, pH, cyclic, and ion interference experiments indicate that the Co3O4–350 °C/PMS system exhibits a wide potential application range. Free radical scavenging experiments show that ·O2− is the main active oxygen species. Co3O4–350 °C as a PMS activator is a catalytic material with large-scale practical applications.